Change in the Mobility of Polish Residents during the Covid-19 Pandemic - Gorzelanczyk, Piotr (Communications - Scientific Letters of the University of Zilina, 2022)
The aim of the article is to analyze the mobility of Polish residents and a change caused by the COVID-19 pandemic. For this purpose, a questionnaire study was conducted on changes in the mobility of Polish residents before and during the COVID-19 pandemic. It was carried out in December 2020, when the second wave of cases of the above-mentioned virus was ongoing in Poland. During the study of Polish residents, questions were asked about the purpose of their trip, means of transport, distance to the destination and duration of the trip, as well as the place of making purchases before and during the pandemic. In addition, respondents were asked whether the COVID-19 pandemic had affected their mobility. During the COVID-19 pandemic, the mobility of citizens, especially in the cities, has changed. Instead of using the public transport, they used cars, bicycles and walk.
Keywords: mobility; Poland; COVID-19; coronavirus; pandemic